69 G-6A POLYMORPHISM OF THE ANGIOTENSINOGEN GENE MODULATES THE EFFECT OF BLOOD PRESSURE ON CAROTID ARTERY INTIMA-MEDIA THICKNESS: THE BOGALUSA HEART STUDY. Issue 1 (1st January 2007) - Bhuiyan, A. R.; Chen, W.; Srinivasan, S. R.; Rice, J.; Boerwinkle, E.; Berenson, G. S.
Abstract : Background: The adverse association between blood pressure and carotid artery intima-media thickness (IMT), a surrogate marker of subclinical arteriosclerosis, is well known. However, whether G-6A polymorphism of the angiotensinogen ( AGT ) gene, a candidate gene involved in the renin-angiotensin system, modulates this relationship is unknown. Methods: This aspect was examined in a 680 white and black subjects, aged 25 to 43 (73.4% white, 39.7% male). Common carotid IMT was measured by B-mode ultrasonography. In addition, the genotyping of G-6A polymorphism of the AGT gene and traditional CV risk factors were performed. Results: Mean arterial blood pressure was significantly associated with common carotid IMT in whites, blacks, and the total sample. The A-6 allele frequency was higher in blacks compared with whites (0.85 vs 0.45, p < .0001). In bivariate analysis, there was no difference in mean arterial blood pressure and common carotid IMT between carriers and noncarriers of AA genotype in whites, blacks, or the total sample after adjusting for gender, age, and race. In multivariate regression analysis, which included gender, age, mean arterial blood pressure, BMI, LDL cholesterol, triglycerides/HDL cholesterol ratio, homeostasis model assessment of insulin resistance, smoking, and race (in total sample), mean arterial blood pressure was significantly and adversely associated with common carotid IMT in whites and blacks. Carriers of AA genotype did not show this association. Furthermore, the adverse positive relationship between mean arterial blood pressure and common carotid IMT was noted among carriers of the AA genotype (comparison of slopes p = .02) only in the total sample. Conclusion: These results indicate that allelic variation (G-6A) of the AGT gene modulates the association between carotid IMT and mean arterial blood pressure in young adults.